A critical ethnography of young adolescents' occupational choices in a community in post-apartheid South Africa - Galvaan, Roshan (Division of Occupational Therapy, 2014)
This thesis explored the occupational choices of young adolescents in a southern peninsula Cape Town community of Lavender Hill in South Africa. Informed by current research and prior professional and personal experiences with young adolescents in Lavender Hill, the research question asked: 'What informs occupational choice among young adolescents in Lavender Hill?' This complemented the research aim, which was to generate insight into the nature of the occupational choices of a group of young adolescents in Lavender Hill, and the factors that influenced their occupational choices.